An Error Analysis of the Use Of Present Participle Form of the Sixth Semester Students of FKIP Universitas Bandar Lampung - Miryanti Feralia (International Conference on Education and Language (ICEL), 2014)
The purpose of this research was cooperated the investigation of the error analysis of the use of present participle form of the sixth semester students of FKIP Universitas Bandar Lampung 2014.The data were collected by incorporating tests to measure the students’ error in using present participle form based on surface strategy taxonomy. They did the structure tests that were a set of Indonesian sentences to be translated into English.Data analysis was conducted using two techniques. They were identifying the students’ errors based on surface strategy taxonomy and finding the dominant type. The result indicated that from 16 students’ works, it was found 244 errors. Theses errors were classifed into 4 kinds of errors: omission wa 20 (8,20%), addition was 2 (0,82%), misformation was 221 (90,57%), and misordering was 1 (0,41%). It meant that misformation is the most frequent error while the least error is misordering.It can be concluded that students’ grammar mastery specially present participle form was still low. It suggested that the lecturers had to emphasize in teaching present participle form for the students. For the students, although present participle was the easiest part of grammar they had to be aware to understand it well.